Endometrial carcinoma: diffusion-weighted imaging diagnostic accuracy and correlation with Ki-67 expression. Issue 4 (April 2018) - Jiang, J.X.; Zhao, J.L.; Zhang, Q.; Qing, J.F.; Zhang, S.Q.; Zhang, Y.M.; Wu, X.H.
Abstract : Aim: To evaluate the role of diffusion-weighted imaging (DWI) in the detection of endometrial carcinoma and to correlate the apparent diffusion coefficient (ADC) value with Ki-67 expression. Materials and methods: Fifty-two patients with invasive cancer who underwent pelvic MRI were prospectively evaluated using DWI with b-values of 0 and 1000 s/mm 2. The ADC values from standard DWI were measured. The expression of Ki-67 in histological specimens was analysed using immunohistochemistry. The ADC values of endometrial carcinoma and normal endometrial parenchyma were compared. Relationships between ADC values and Ki-67 expression were determined using Wilcoxon's signed rank test and the Kruskal–Wallis test. Results: Endometrial carcinoma was detected at DWI as a hyperintense area in 92.3% (48/52) of patients. There was a significant difference in the mean ADC values between endometrial carcinoma and normal endometrial parenchyma (1.39±0.27×10 −3 versus 0.93±0.21×10 −3 mm 2 /s, p< 0.001). The mean ADC values of grade 1 patients were significantly higher than those of grade 3 patients (1.01±0.16×10 −3 versus 0.83±0.21×10 −3 mm 2 /s, p< 0.05). The mean ADC values of stage IB patients were significantly lower than those of stage IA patients (0.86±0.16×10 −3 versus 1.04±0.21×10 −3 mm 2 /s, p< 0.01). The mean ADC values of high Ki-67 expression patients were significantly lower than those of low Ki-67 expression patients (0.82±0.12×10 −3 versus 1.16±0.12×10 −3 mm 2 /s, p< 0.001). There was a significant negative correlation between the mean ADC value and Ki-67 expression ( r=– 0.82, p< 0.001). Conclusion: The ADC value was a helpful parameter for detecting the tumour grade, stage, and proliferation of endometrial carcinoma, and may further improve patient prognosis and contribute to the development of more effective treatment programmes. Highlights: There was a significant difference in the mean ADC values between endometrial carcinoma and normal endometrial parenchyma. The mean ADC values of Grade 1 patients were significantly higher than those of Grade 3 patients and the mean ADC values of stage IB patients were significantly lower than those of stage IA patients. There was a significant negative correlation between the mean ADC value and Ki-67 expression. The ADC value was a helpful parameter for detecting the endometrial carcinoma and may further improve patient prognosis.